The Effect of Institutional Environment, General Self Efficacy and Desirability On Social Entrepreneurship Intentions in Turkey - Aydın Kayabaşı; Ceren Karavelioğlu; N. Derya Ergün Özler (Istanbul Business Research)
The purpose of this study is to explore the impact of the institutional environment on general self-efficacy and desirability as well as the impact of general self-efficacy and desirability on social entrepreneurship intentions. For data collection a structured questionnaire was used. In total 500 questionnaires were distributed among university students and 367 usable questionnaires were returned and analysed. The structural equation modelling was used to investigate the relationship between the study variables. The findings revealed significant relationships among the research variables. It was found that the dimension of the regulatory environment has a positive impact on desirability and the dimension of the cognitive environment has a positive impact on general self-efficacy. The findings also showed a positive relationship among general self-efficacy, desirability and social entrepreneurship intentions. This study was carried out by using a convenience sampling method on university students. Within the scope of the research, the variables of the institutional environment, general self-efficacy and desirability are discussed in terms of social entrepreneurship intention. The study provides a new understanding of the factors that affect the intention of social entrepreneurship and provides an insight into which variables can be prioritized in countries with problems such as environmental pollution, migration and unemployment.